OC-156 Analysis of colorectal polyps detected in the English NHS bowel cancer screening programme with emphasis on advanced adenoma and polyp cancer detected. (28th May 2012) - Majumdar, D; Patnick, J; Nickerson, C; Rutter, M D
Abstract : Introduction: Colorectal cancer is the second most common cause of cancer related death in the UK causing around 16 000 deaths each year. Colorectal adenomas are slow growing precursor lesions which progress to cancer. The lesion of most interest in this context is advanced adenoma (size 10+ mm/with 20%–25% villous histology/high grade dysplasia) as they are of higher risk of progression (2). This study analysed adenomatous lesions detected in NHS BCSP programme. Methods: Data on each patient entering the NHS BCSP programme is prospectively recorded on the national BCSP database. The database was interrogated for all polyps/adenomas found during the period September 2006 to September 2011. The data were analysed with particular focus on detection of advanced adenoma and polyp cancers. Results: A total of 65 535 polyps were found, of which 43 954 (67.06%) were confirmed histologically as adenomas. 15 261 advanced adenomas were detected. These accounts for 34.7% of lesions removed and 23.9% of all lesions detected during screening. 842 polyp cancers were found and removed. 1.9% of the adenomatous lesions removed were polyp cancer. The incidence of villous morphology, HGD and polyp cancer, categorised by adenoma size, are shown in the Abstract OC-156 table 1 . The presence of villous histology and high grade dysplasia increases with increasing size of adenoma, whereas villous histology begins to plateau for adenomas over 15 mm in size, the incidence of HGD appears linear up to and beyond adenomas of 45mm in size. Conclusion: 67.06% of all lesions found were histologically confirmed colorectal adenomas. One third of adenomas were advanced adenomas. There is a trend of increase of incidence of cancer and features of advanced neoplasia in adenomas with increasing size. The incidence of AA feature present in lesions below 10mm in size was 10.07%. Competing interests: None declared. References: 1. Office of National Statistics . UK, 2010. 2. Atkin W, Marson B, Cuzick J. Long term risk of colorectal cancer after excision of ectosigmoid adenomas. N Engl J Med 1992;326 :658–62.